African-American Literature and Slavery in Saudi Arabia: A Literary-Historical Analysis Using Critical Race Theory - Menia Mohammad Almenia (International Journal of Linguistics, Literature and Translation, 2025)
Literature and life influence and mirror each other so profoundly that the line between fact and fiction is often blurred. This study examines how the anti-slavery literary tradition of mid-twentieth century shared a complimentary relationship with international slavery abolitionist efforts, most notably the transnational efforts of the British Anti-Slavery Society to abolish Saudi slave trade during the 1950s taking vantage of Bell’s Critical Race Theory. Decolonization of Saudi Arabia at this time led to sustained tensions between human rights advocacy and assertions of national sovereignty which sparked a global humanitarian debate. The primary data in the study comes from two narrative sources: One, archival texts including Saudi diplomatic correspondence, United Nations records, consular reports, and contemporaneous government statements. Two, three contemporary novels viz., Native Son, Invisible Man, and Black Boy are included as samples of a parallel literary tradition in African-American literature within which these political efforts are mirrored. With articulations on racism, bondage, and morality, these texts are treated not merely as socio-cultural artifacts but also as theoretical interventions that informed social and political interpretations of slavery. Analyses indicate collapse of anti-slavery mechanisms despite freedom of Saudi Arabia until transnational and inter-racial coalitions mediated through literary imagination to construct human rights narratives that influenced policy debates on abolitionism an eventually enforced abolition of slavery.